Efektivitas Buku Saku Perilaku Profesional Caring Perawat Model “Praktis” terhadap Peningkatan Pengetahuan Perawat - Fajar Yousriatin; Hendra Priyatnanto; Diena Juliana (Universitas Malahayati Lampung, 2025)
ABSTRACT Nursing care is a crucial element in patient recovery. In Islam, the nursing care informed by the Quran and Sunnah is regarded as Islamic Caring, representing a professional conduct that demonstrates intellectual competence in delivering nursing services to patients, families, and communities in compliance with Islamic principles. This study aims to assess the efficacy of the